Clinical and genetic associations of dipeptidyl peptidase-4 inhibitor treatment response in type 2 diabetes / Jazlina Liza Jamaluddin - Jazlina Liza , Jamaluddin (2017)
Incretin-based therapies are a recent class of antidiabetic agents that modulate glucose homeostasis in type 2 diabetes (T2D) via the incretin pathway. Oral incretin-based therapy namely the dipeptidyl peptidase-4 (DPP-4) inhibitors, block the DPP-4 enzyme, thus preventing the degradation of active glucagon-like peptide-1 (GLP-1) and glucose-dependent insulinotropic peptide (GIP), thereby activating the expression of multiple genes resulting in insulin secretion, β-cell proliferation, and survival. Despite the wide use of DPP-4 inhibitors, little is known of clinical and pharmacogenomic factors that specifically associated with DPP-4 inhibitor treatment response, especially in Malaysian subjects. Aim: The aim of this study is to determine the clinical and genetic associations of DPP-4 inhibitor treatment response in Malaysian with T2D. Based on disease pathogenesis and the incretin pathway, we hypothesized that three genes, DPP4, WFS1, and KCNJ11, play a role in the response to DPP-4 inhibitors. The genes include the drug target, pathway genes, and disease genes. We also hypothesized that two main clinical factors, dipeptidyl peptidase (sCD26) and homeostasis model assessment of insulin resistance (HOMAIR), would be associated with the response to DPP-4 inhibitors. The selection of these clinical factors was based on an understanding of the disease pathogenesis and the mechanism of drug action. Patients and methods: In this observational cross-sectional study, we recruited 331 patients with T2D who had been treated with DPP-4 inhibitors (sitagliptin, vildagliptin and linagliptin) for at least 3 months and 331 control subjects with T2D treated with oral non-DPP-4 inhibitor therapies. All participants were recruited from the Diabetes Clinic (tertiary care) at the University of Malaya Medical Centre (UMMC), Malaysia. All subjects were genotyped for DPP4, WFS1 and KCNJ11 gene polymorphisms. Genotyping was performed by Applied Biosystems TaqMan SNP genotyping assay. Fasting venous blood samples were taken from all subjects for the determination of A1c, fasting plasma glucose iii (FPG), fasting insulin, fasting lipids, liver enzymes and sCD26. Results: 44.7% experienced good glycemic control with DPP-4 inhibitor therapy. Upon univariate analysis; triglycerides, waist circumference, LDL cholesterol, aspartate aminotransferase (AST), DPP-4 inhibitor regimens (with biguanide + sulphonylurea with/without thiazolidinedione), WFS1 rs734312 and KCNJ11 rs2285676 predicted response to DPP-4 inhibitor therapy (defined as A1c <7%). Upon multivariate analysis, patients with triglycerides levels less than 1.7 mmol/L (OR: 2.4; 95% CI: 1.152–5.097), and KCNJ11 rs2285676 (genotype CC) (OR: 2.0; 95% CI: 1.065-3.856) were found to be more likely to respond to DPP-4 inhibitor treatment compared with other patients. Triglyceride and KCNJ11 rs2285676 (genotype CC) gene polymorphism were not associate of good glycemic control (A1c <7%) in the control group. Conclusions: An overall model of DPP-4 inhibitor treatment response was developed using clinical and genetic variables to determine the optimal DPP-4 inhibitor treatment response in patients with T2D. From this model, patients with T2D most likely to benefit from DPP-4 inhibitor treatment are those with a KCNJ11 rs2285676 (genotype CC) gene polymorphism and triglycerides values within normal range. These pharmacogenomic findings by identifying those most likely to respond to DPP-4 inhibitor treatment will enable cost-effective personalized treatment of patients with T2D.